Ultraestructura del tegumento de la metacercaria,juvenil y adulto de Clinostomum complanatum (Trematoda: Clinostomidae) - Segovia-Salinas, Feliciano (1993)
The integuments of metacercariae, juveniles and adults of Clinostomum complanatum are described. The metacercariae have a large number of invaginations and below these a great number of vesic1es. The surface of the integument is covered with microvilli in the young worm of 3-4 ciays and in the adult of 8 days postinfection. The mitochondria were found in the basal lamina and its bridges; they are round, oval or elongate and have several crests irregular1y arraílged. Few mitochondria occur in the metacercarial stage and the adult, while many are seen in the young. The basal lamina thickens slighdy in conformity with growth. The perinuc1ear cytoplasm contains an ovoid nucleus with one nucleolus and vesícles. The surface of the 3-day postinfection young worms has an extraintegumental layer. The triangle-shaped cuticular spines were scarce and irregular1y placed. They are also observed in metacercariae and young worms of 1-3 days. In the adults, microvillae are present in the external surface, they have diffuse vacuoles in the basal layen, and the basal lamina thickens slighdy as it grows.